Evaluation of DementiaNet, a network-based primary care innovation for community-dwelling patients with dementia: protocol for a longitudinal mixed methods multiple case study. Issue 8 (4th August 2017) - Richters, Anke; Nieuwboer, Minke S; Perry, Marieke; Olde Rikkert, Marcel G M; Melis, Rene J F; van der Marck, Marjolein A
Abstract : Introduction: Primary healthcare professionals will increasingly be required to manage and optimise their treatment for patients with dementia. With DementiaNet, we aim to reduce the burden of dementia on healthcare services and society through implementation and facilitation of integrated network-based care with increased dementia expertise. DementiaNet is designed as a stepwise approach including clinical leadership, quality improvement cycles and interprofessional training, which are tailor-made to the local context. For example, the composition of the network and improvement goals are tailored to the local context and availability. Here, we describe the linked evaluation study which aims to provide insight in effectiveness, process and mechanism of the DementiaNet approach through an innovative evaluation design. Methods and analysis: We designed a longitudinal, mixed methods, multiple case study. Study population consists of two levels: (i) local DementiaNet networks of primary care professionals and (ii) patients and informal caregivers who receive care from these networks. At the start and after 12 and 24 months, quantitative data are collected for each network on: level of network maturity, quality of care indicators and outcomes reported by informal caregivers of dementia patients. We assess changes in networks over time and the association with quality of care and informal caregiver-reported outcomes. Throughout the study, logs about each network are registered. Additionally, semi-structured interviews with network members and informal caregivers will provide insight in experiences and opinions regarding effects and mechanisms through which changes in quantitative outcomes are effectuated. Rich narratives will be constructed about the development of the local networks using collected data. Ethics and dissemination: The study protocol was reviewed by the local medical ethics committee; formal judgement was not required (protocol number: 2015–2053). The findings of this study will be disseminated through peer-reviewed publications, conference presentations and presentations for healthcare professionals where appropriate.